2015
DOI: 10.1136/archdischild-2015-310148.6
|View full text |Cite
|
Sign up to set email alerts
|

Invasiveness of Pharmacokinetic Studies in Children–a Systematic Review

Abstract: Objectives: To explore whether pharmacokinetic (PK) studies in paediatric patients are becoming less invasive. This will be evaluated by analysing the number of samples and volume of blood collected for each study within four different decades.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…A useful survey by Altamimi et al found that across age groups there was no difference in the collected volume per sample or per child, while a significant difference was found in the frequency of sampling between sparse PK sampling (also known as population PK) and traditional intensive PK sampling studies in children. This suggests that clinical pharmacologists should emphasize the use of population‐based approaches to optimize the blood collection time‐points to avoid the limitations described above.…”
Section: Clinical Pharmacology Considerationsmentioning
confidence: 99%
“…A useful survey by Altamimi et al found that across age groups there was no difference in the collected volume per sample or per child, while a significant difference was found in the frequency of sampling between sparse PK sampling (also known as population PK) and traditional intensive PK sampling studies in children. This suggests that clinical pharmacologists should emphasize the use of population‐based approaches to optimize the blood collection time‐points to avoid the limitations described above.…”
Section: Clinical Pharmacology Considerationsmentioning
confidence: 99%
“…Some achievements were highlighted by Cheng et al on vaccination for Haemophilus nfluenzae type b and rotavirus, personalized medicine and immunotherapies for acute lymphoblastic leukemia, improved prevention of HIV transmission from mother to baby, and increasing life expectancy for children with chronic diseases such as cystic fibrosis and sickle cell disease. These tools allow for more precise and detailed laboratory measurements and medical images of clinical pharmacokinetic (PK) and pharmacodynamic (PD) observations from birth to adolescence to assess the impact of age/maturation on drug action and disease progression with the goal of ensuring safety and effectiveness of investigated products in this vulnerable population. Despite these efforts, improvements/optimization of the quantitative approaches to use these data across literature, clinical trials, and hospitals records are still desired.…”
mentioning
confidence: 99%